PENINGKATAN LITERASI KEUANGAN BAGI GENERASI MUDA MELALUI PEMBELAJARAN MANAJEMEN KEUANGAN DASAR PADA PONDOK PESANTREN MODERN KULLIYYATUL AL-NAASYIIN AL-ISLAMIYYAH (KULNI) - Riski Wisnu Prakoso; Lailatul Uyun (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
Financial literacy and understanding of basic financial management are crucial competencies for the younger generation to prepare for a better and more independent financial future. However, many students in Islamic boarding schools still have limited understanding in managing personal finances, such as budgeting, recording income and expenses, and distinguishing between needs and wants. This Community Service Program (PKM) aims to provide socialization and education regarding the importance of financial literacy and the application of basic financial management for the younger generation. Through an approach based on interactive lectures, discussions, simple case studies, and simulations of allowance management, this program helps participants understand the basic principles of financial management, cultivate saving awareness, and develop wise and responsible financial behavior.The Community Service Program (PKM) was conducted on April 17, 2026, at the Kulliyyatul Al-Naasyiin Al-Islamiyyah (KULNI) Modern Islamic Boarding School. The methods used in this program included counseling, interactive workshops, and practical exercises in simple budgeting and financial recording. Evaluation through pre-tests and post-tests, as well as observation of participant engagement, was carried out to measure the improvement in participants' understanding and changes in financial behavior. The expected outcomes are an increase in students' awareness and skills in managing their finances in a planned and responsible manner, thereby fostering healthy financial habits from an early age and preparing them to become financially independent individuals in the future